ANALISIS KERAGAAN AGROINDUSTRI KOPI LUWAK : STUDI KASUS PADA AGROINDUSTRI RATU LUWAK DI KECAMATAN BALIK BUKIT KABUPATEN LAMPUNG BARAT - Arief Laksono; Fembriarti Erry Prasmatiwi; Yuliana Saleh (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2022)
This study aimed to analyze management of raw material procurement; cost of production, added value and profit; distribution channels in the luwak coffee aroindustry. The method used was a case study on the Ratu Luwak Agroindustry in Balik Bukit District, West Lampung Regency. The research was conducted from April 2020 to June 2020. The data analysis methods used were quantitative and qualitative descriptive analysis. The results of this study indicated that the management of raw material procurement was not yet economical; the cost of production, added value and profit of the agroindustry had positive values which means that the agro-industry was profitable; distribution channels shown that the marketing was efficient. Key words: agroindustry, luwak coffee, performance, regular coffee.